Serum and cervico-vaginal glycodelin concentrations as predictors of successful implantation after embryo transfer - Amr H. Farag; Ali Farid; Mohamed H. Nasr El-Din; Marwa A. Mohamed; Amr M. El-Helaly (Elsevier, 2022)
Objective: Evaluation of glycodelin (Gd) concentrations in serum and cervico-vaginal secretions as a predictor for implantation after ICSI. Materials and methods: Prospective study on 50 women undergoing ICSI where long protocol ovarian stimulation was used. Serum and cervico-vaginal lavage Gd concentrations were measured then rates of biochemical and clinical pregnancy were detected and predictive value was evaluated using logistic regression analysis. Results: Using cut-off values of 2.2 ng/ml and 1.9 ng/ml for serum and cervico-vaginal Gd concentrations respectively for biochemical pregnancy and values of 2.7 ng/ml and 1.3 ng/ml respectively for clinical pregnancy, there was no significant difference regarding sensitivity (72% & 56%, and 72% & 89%, respectively and respectively). Specificity was statistically similar for biochemical pregnancy (72% and 89%, respectively) while specificity was significantly higher for clinical pregnancy using cervico-vaginal Gd concentration of 1.3 ng/ml (88%) compared to serum Gd concentration of 1.9 ng/ml (53%). Conclusion: Glycodelin appears to be a promising marker for implantation after IVF/ICSI.